(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Education is an important part of life which make life better and primary education is the foundation stage of children but many students are not able to get this education for various reasons that’s why government make one scheme which name is MID DAY MEAL which helps to increase the enrolment number of students in school. The research aims to study the implementation of the Mid-Day Meal Scheme in Government primary schools of the Udalguri district of Assam. Methodology: For the purpose study descriptive and theoretical methodology is used. The researcher used self-structured questionnaire for collection of data. Tables are used to analyze the collected data and effectiveness of this scheme. Main Findings: Results showed that Mid-Day Meal Scheme is playing an important role in decrease classroom hunger of students. Main motto of the scheme is to increase the enrolment number in primary education. Applications of this study: This research can be used by policymakers, teachers, parents and also social welfare activities. Originality of this study: For the first time, implementation of the Mid-Day Meal Scheme has been studied in the Udalguri district of Assam